Genome‐scale model of C. autoethanogenum reveals optimal bioprocess conditions for high‐value chemical production from carbon monoxide. Issue 2 (20th June 2019) - Norman, Rupert O.J.; Millat, Thomas; Schatschneider, Sarah; Henstra, Anne M.; Breitkopf, Ronja; Pander, Bart; Annan, Florence J.; Piatek, Pawel; Hartman, Hassan B.; Poolman, Mark G.; Fell, David A.; Winzer, Klaus; et al.
Abstract : Clostridium autoethanogenum is an industrial microbe used for the commercial‐scale production of ethanol from carbon monoxide. While significant progress has been made in the attempted diversification of this bioprocess, further improvements are desirable, particularly in the formation of the high‐value platform chemicals such as 2, 3‐butanediol (2, 3‐BD). A new, experimentally parameterised genome‐scale model of C. autoethanogenum predicts dramatically increased 2, 3‐BD production under non‐carbon‐limited conditions when thermodynamic constraints on hydrogen production are considered.